Analysis for science, engineering and beyond the tribute workshop in honour of Gunnar Sparr held in Lund, May 8-9, 2008 - Persson, Lars-Erik; Silvestrov, Sergei D.; Astrom, Kalle (Springer Proceedings in Mathematics, 2012)
This book project was initiated at The Tribute Workshop in Honour of Gunnar Sparr and the follow-up workshop Inequalities, Interpolation, Non-commutative Analysis, Non-commutative Geometry and Applications, held at the Centre for Mathematical Sciences, Lund University in May and November of 2008.  The resulting book is dedicated in celebration of Gunnar Sparr's sixty-fifth anniversary and more than forty years of exceptional service to mathematics and its applications in engineering and technology, mathematics and engineering education, as well as interdisciplinary, industrial and international cooperation.   This book presents new advances in several areas of mathematics and engineering mathematics including applications in modern technology, engineering and life sciences.  Thirteen high-quality chapters put forward many new methods and results, reviews of up to date research and open directions and problems for future research. A special chapter by Gunnar Sparr and Georg Lindgren contains a historical account and important aspects of engineering mathematics research and education, and the implementation of the highly successful education programme in Engineering Mathematics at Lund Institute of Technology,  where not only the mathematical sciences have played a role. This book will serve as a source of inspiration for a broad spectrum of researchers and research students.